Preparation of high encapsulation efficiency fragrance microcapsules and their application in textiles. Issue 84 (26th August 2016) - Zhao, Di; Jiao, Xin; Zhang, Miaomiao; Ye, Kai; Shi, Xiaodi; Lu, Xihua; Qiu, Gao; Shea, Kenneth J.
Abstract : Poly(1, 4-butanediol dimethacrylate) (PBDDMA) microcapsules with PBDDMA as the shell and dementholized peppermint oil (DPO) fragrance as the core material have been synthesized through a novel interfacial free-radical polymerization. Abstract : Poly(1, 4-butanediol dimethacrylate) microcapsules containing dementholized peppermint oil (DPO) were prepared by interfacial free-radical polymerization. The influence of the composition of the core material on the morphology of the fragrance microcapsules was investigated by scanning electron microscopy (SEM). Response surface methodology (RSM) was applied to optimize the effects of curing temperature, homogenization time, ratio of core/shell and homogenization rate on the encapsulation efficiency. The thermal stability of the fragrance microcapsules was studied by thermogravimetric analysis (TGA). The prepared fragrance microcapsule, under optimal conditions, possessed spherical shape, good thermal stability below 100 °C and high encapsulation efficiency of 91%. In addition, the fragrance microcapsules coated onto cotton fabric displayed good washing durability after 15 cycles, which will be beneficial for their future application in textiles, daily necessities and so on.